Relación de la vacuna para la influenza A (H1n1) y las infecciones respiratorias (gripe, neumonías) en menores de 5 años - La Libertad 2009 - Villacorta Esteves, Milagro Del Pilar (2013)
"Relationship of the Influenza Vaccine (H1N1) and respiratory infections_x000D_ (influenza, pneumonia) in under 5 La Libertad 2009"._x000D_ For the development of the research information from the study was_x000D_ collected, "Risk of Vaccine-Preventable Diseases 2009," based on_x000D_ experience and on the global problem of pandemic influenza, it was decided_x000D_ to supplement the study the following research with the main objective of_x000D_ finding the relationship of the vaccine against the Influenza A (H1N1) and_x000D_ respiratory infections (flu, pneumonia) in children under 5 years, La Libertad_x000D_ 2009._x000D_ Out our population consisted children under 5 years (155.627 habt.)_x000D_ Obtaining a sample of 9 health facilities, of which 8.650 children participated_x000D_ in the study, using the technique of sampling by conglomerates systematic_x000D_ aleatory._x000D_ To find the relationship of the vaccine against the Influenza A (H1N1) and_x000D_ respiratory infections (flu, pneumonia) they worked with the nonparametric_x000D_ chi-square, being found a significant relationship among these 2 variables._x000D_ It was determined that the ratio of the vaccine for the Influenza A (H1N1) in_x000D_ children under 5 years was significantly associated with the flu, but not with_x000D_ pneumonia, after application of the vaccine for the Influenza A (H1N1), the_x000D_ incidence of HCAI in under 5 was reduced by 17.92%, 97% of the population_x000D_ would be willing to be vaccinated, the vaccination is no cause for to the fear_x000D_ of the vaccine (71%), and the reason for the defection to vaccines in children_x000D_ under 5 years is ignorance (date of vaccination, vaccine fear of)